The Cytotoxic Effect of the Tarragon (Artemisia dracunculus L.) Hydroalcoholic Extract on the HT-29, MKN45, and MCF-7 Cell Lines - Farzaneh Motafeghi; Emran Habibi; Maryam Firozjaei; Mohammad Eghbali; Parham Mortazavi; Amirhossein Salmanmahiny; Mohammad Shokrzadeh (Mazandaran University of Medical Sciences, 2023)
Background::Cancer is one of the problems facing societies today and despite new advances in chemotherapy and cancer treatment, there are still many cancers that do not respond to today's treatments. Tarragon with the scientific name of Artemisia dracunculus L. has various flavonoid and polyphenolic compounds and many therapeutic effects.  Objectives: This study aimed to investigate the cytotoxicity of this plant on different categories of cancer cels. Methodes: After collecting the shoots of tarragon and extracting them by the maceration method, the weight of the extract with a yield of 22.25% was 12.9 g. After examining the presence of flavonoids and total phenol, the extract's antioxidant activity was examined using DPPH and FRAP methods. Finally, MTT tests on three cancer cell lines, MCF-7, HT-29, and MKN45, were done using different concentrations of tarragon extract (100, 200, 500, and 1000 μg/mL). Results: Total flavonoids were detected at 24±1.18 mg of quercetin per gram of extract, and total phenols were detected at 59±2.21 mg of gallic acid per gram of extract. Examining the inhibitory effect of DPPH compared to vitamin C, it was found that the hydroalcoholic extract of tarragon has a 50% inhibitory effect. According to the standard curve, the amount of iron reduced by tarragon hydroalcoholic extract is equal to 405±0.11 μg/ml. The cytotoxic effect of tarragon hydroalcoholic extract on MCF7, MKN45, and HT-29 cell lines was investigated, and their IC50 values were 1065.669, 881.19, and 743.870 μg/mL, respectively. The A. dracunculus L extract inhibits the growth of cancer cells in various cell lines.  Conclusion: According to antioxidant tests, it can be said that the anti-cancer effects of tarragon are based on its antioxidant power and phenolic and flavonoid compounds.